2021
DOI: 10.1021/acssuschemeng.1c01978
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High-Alkaline Stable Quaternized Poly(arylene ether ketone)/Graphene Oxide Derivative Including Zwitterion for Alkaline Fuel Cells

Abstract: Anion-exchange membrane fuel cell (AEMFC) systems have emerged as a promising alternative for proton-exchange membrane due to their reasonable manufacturing cost and fast oxidation−reduction reactions. But, polymer backbone with ether linker-based poly arylene ether is quickly decomposed in high alkaline media, limiting the commercialization possibilities. Herein, a series of anion-exchange composite membranes having a graphene oxide derivative [graphene oxide linked with methyl orange (GO-MO) containing zwitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…It is known that the hydroxide can transport in AEMs via either the vehicular mechanism or the Grotthuss mechanism [57]. Previous studies suggested that the ion transport will obey vehicular mechanism if the activation energy is less than 14 kJ mol −1 [58,59]. Since the activation energies in these two membranes exceed 14 kJ mol −1 , the Grotthuss mechanism is supposed to dominate the ion transport mechanism [60].…”
Section: Hydroxide Conductivity and Alkaline Stabilitymentioning
confidence: 99%
“…It is known that the hydroxide can transport in AEMs via either the vehicular mechanism or the Grotthuss mechanism [57]. Previous studies suggested that the ion transport will obey vehicular mechanism if the activation energy is less than 14 kJ mol −1 [58,59]. Since the activation energies in these two membranes exceed 14 kJ mol −1 , the Grotthuss mechanism is supposed to dominate the ion transport mechanism [60].…”
Section: Hydroxide Conductivity and Alkaline Stabilitymentioning
confidence: 99%
“…The GO nanosheets could resist continuous attacks to the structure of QPPO from hydroxyl groups. 48 Furthermore, the retention ratios were 94.1% for SEBS-C16-20C4 59 and 94.9% for Cr-ASD-PSF2.05. 60 In our opinion, the results could inspire the further research on enhancing alkaline stability of the AEM through preparing GO-based composites.…”
Section: Alkaline Stabilitymentioning
confidence: 92%
“…Thus the developments of a wide variety of quaternary ammonium functionalized polymers, such as poly(arylene ether sulfone), poly(arylene ether ketone), poly (p-phenylene-co-aryl ether ketone), poly(isatin biphenylene), poly(ether ether ketone), and poly(phenylene oxide) are considered for AFC applications [ 145 , 146 , 147 , 148 , 149 , 150 ]. Recently, several nano- or micro-fillers were tested in composite AEMs to improve the performance of AFCs even more [ 151 , 152 , 153 , 154 , 155 ]. In this connection, the surface-modified different bioinspired materials, specifically quaternized, have been developed to be evaluated in the AFC system with and without additives and other polymers.…”
Section: Developments Of Anion Exchange Membranes With Modified Cellu...mentioning
confidence: 99%